Pembelajaran Pengolahan Data dengan Metode Permainan Pos Berantai pada Siswa Kelas 4 Sekolah Dasar - Unaenah, Een; Marctines, Gabriella Sinthia; Nahzifa, Nanda (MASALIQ, 2023)
Data processing is an important aspect of learning mathematics at the elementary school level. Next will understand mathematics in data processing. Data processing is the process of collecting, compiling, analyzing, and presenting data in graphical or tabular form so that it is easy to understand. There are two types of data that are often used in data processing, namely qualitative data and quantitative data. Qualitative data are those that are measured based on research as they are and cannot be measured by numbers, such as color, smell, and taste. Meanwhile, quantitative data is data that can be measured based on numbers, such as numbers or sizes. There is a method that can be used to better understand interactive data processing, namely the serial post game method. With this method in order to be able to explore the use of the postal game method in teaching data processing to grade 4 students in elementary schools so that it is more fun and does not make students easily bored. There is also the purpose of this study is to know how to improve learning outcomes in mathematics lessons regarding data processing using the serial post method for class IV Elementary School and to find out the responses to mathematics lessons on data processing materials that link students' activeness.